Bengali sign language translator with location tracking system - Tanim Rahman; Tanjia Chowdhury; Jeenat Sultana (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Designing an embedded system to convert sign language to sound forms to communicate with the outside world can be a challenging yet rewarding project, especially for mute people. To convey a speaker's thought through sign language, hand shapes, hand orientation and movement, and facial expressions must be combined concurrently. This research is intended to design a system that translates sign language into sound forms to establish communication with the outside world for people who are deaf, those who can hear but cannot physically speak, or have trouble with spoken languages due to some other disabilities. They can thus receive prompt assistance and stay out of uncomfortable circumstances. Additionally, this system incorporates a tracking system that uses a global system for mobile communications (GSM)/ global positioning system (GPS) module to locate a person using a tracking device and send the location to previously saved emergency contact numbers so that someone nearby can quickly locate and assist the person. Typically, each nation has its own native sign language. This project will create a few essential and typical sentences and phrases in Bengali.